From start-up nation to sports-tech nation? A SWOT analysis of Israel's use of sports for nation branding. (5th April 2021) - Dubinsky, Yoav
The study analyses the role of sports in the branding of Israel. For almost three millennia, countries, cities and communities have been using sports to improve their images. Israel's image is deteriorating as the Israeli-Arab dispute escalates, partly due to not having clearly communicated nation branding strategies. In this qualitative study, I conducted 14 semi-structured interviews with officials in key policy-making positions in Israeli sports and in the Israeli government. Based on the thematic analysis, I conducted a SWOT analysis, and came up with six practical recommendations for Israel. With Israel being a world leader in start-up companies' per-capita and with sports organisations recognising the potential of Israel becoming a technological greenhouse, one of the key recommendations is to brand Israel as a sports-tech nation. Although the study focuses on Israel, other countries facing prolonged conflicts should also consider the recommendations when using sports for nation branding purposes.